Solving engineering problems in dynamics - Spektor, Michael B., 1933- (Industrial Press, 2014)
This comprehensive yet compact step-by-step guide to solving real life mechanical engineering problems in dynamics offers all the necessary methodologies and supplemental information - in one place. It includes numerous solutions of examples of linear, non-linear, and two-degree-of-freedom systems. These solutions demonstrate in detail the process of the analytical investigations of actual mechanical engineering problems in dynamics. It is sure to be a very useful guide for students in Mechanical and Industrial Engineering, as well practitioners who need to analyze and solve a variety of problems in dynamics.
Includes index.
Keywords: Dynamics -- Problems, exercises, etc.; elektronické knihy; electronic books